Avaliação do equilíbrio postural e risco de quedas em indivíduos com deficiência isolada do GH - Brasileiro, Giulliani Antoniceli Moreira (2018)
Growth hormone (GH) and Insulin Growth Factor type I (IGF-I) are peptides that act strongly on structural biosynthesis and on phenotypic parameters such as weight, height, Body Mass Index (BMI), as well as anatomical proportionality . The maintenance of proprioceptive integrity: vestibular, somatosensory, visual and auditory system, when intact and associated with the mentioned characteristics, become important factors for the maintenance of postural balance. This is a cross-sectional, analytical and observational study where the objective was to evaluate anthropometry, body balance and risk of falls in individuals with a specific mutation at the GHRH gene receptor. Sixty individuals, matched by sex, age, IPAQ and BMI, were divided into two groups: Deficiency of GH (DIGH) n: 30 (15 men / 15 women) and Control, residing in Itabaianinha, 40 (20 men / 20 women) with age (46.5 ± 12.4 vs. 43.2 ± 11.2 a), weight (38.0 ± 6.9 vs. 66.6 ± 10.7 kg), height (125.5 ± 7.6 vs. 166.0 ± 10.3 cm), standard deviation of height (SDS height) (-8.6 ± 1.3 vs. -0.3 ± 1.5 H / a), BSA (1.1 ± 0.1 vs. 1.7 ± 0.1 m2), BMI (23.4 ± 3.4 vs. 24.1 ± 2.8 KG / m2). The static balance was evaluated through the force platform apparatus and the risk of falls by the Timed Up and Go (TUG) test. Statistically, to compare the groups, we used the Student's t test with 95% confidence interval and p value <0.05. (P <0.001), lean body mass (25.6 ± 7.2 vs. 53.8 ± 12.1 kg) (p <0.001), mean age of the patients (p <0.001) (p <0.001), and postural oscillation in the open eye parameters (6.8 ± 1.4 vs. 8.0 ± 2.0 mm) (p <0.001), closed eye (7.8 ± 2.6 vs. (P <0.001), as well as for TUG (11.3 ± 2.1 vs. 7.1 ± 1.4 s) (p <0.010), but not for unipodal support (30.4 ± 7.1 vs. 32.4 ± 6.4 mm) ( p = 0.214 Finally, the study showed that IGHD individuals presented lower static stance oscillation without changes in the dynamic balance and risk of falling within the predictive values of normality, concluding that the mutation in the GHRHR gene positively influenced these factors.